Muscle size, strength, and physical performance and their associations with bone structure in the Hertfordshire Cohort Study. (18th October 2013) - Edwards, Mark H; Gregson, Celia L; Patel, Harnish P; Jameson, Karen A; Harvey, Nicholas C; Sayer, Avan Aihie; Dennison, Elaine M; Cooper, Cyrus
ABSTRACT Sarcopenia is associated with a greater fracture risk. This relationship was originally thought to be explained by an increased risk of falls in sarcopenic individuals. However, in addition, there is growing evidence of a functional muscle‐bone unit in which bone health may be directly influenced by muscle function. Because a definition of sarcopenia encompasses muscle size, strength, and physical performance, we investigated relationships for each of these with bone size, bone density, and bone strength to interrogate these hypotheses further in participants from the Hertfordshire Cohort Study. A total of 313 men and 318 women underwent baseline assessment of health and detailed anthropometric measurements. Muscle strength was measured by grip strength, and physical performance was determined by gait speed. Peripheral quantitative computed tomography (pQCT) examination of the calf and forearm was performed to assess muscle cross‐sectional area (mCSA) at the 66% level and bone structure (radius 4% and 66% levels; tibia 4% and 38% levels). Muscle size was positively associated with bone size (distal radius total bone area β = 17.5 mm2/SD [12.0, 22.9]) and strength (strength strain index (β = 23.3 mm3/SD [18.2, 28.4]) amongst women (p < 0.001). These associations were also seen in men and were maintained after adjustment for age, height, weight‐adjusted‐for‐height, limb‐length‐adjusted‐for‐height, social class, smoking status, alcohol consumption, calcium intake, physical activity, diabetes mellitus, and in women, years since menopause and estrogen replacement therapy. Although grip strength showed similar associations with bone size and strength in both sexes, these were substantially attenuated after similar adjustment. Consistent relationships between gait speed and bone structure were not seen. We conclude that although muscle size and grip strength are associated with bone size and strength, relationships between gait speed and bone structure and strength were not apparent in this cohort, supporting a role for the muscle‐bone unit. © 2013 American Society for Bone and Mineral Research